Strategi Pondok Pesantren Bai’aturridhwan Bukittinggi dalam Mengatasi Dampak Negatif Budaya Digital pada Santri - Dendy Maulana; Muhiddinur Kamal (YASIN, 2026)
Although the negative impacts of digital culture on the character and behavior of santri have been widely studied, research specifically analyzing Islamic boarding schools’ strategies for managing and addressing these impacts, particularly at Pondok Pesantren Bai’aturridhwan Bukittinggi, remains relatively limited. This study aimed to analyze the strategies implemented by the Islamic boarding school to address the negative impacts of digital culture on santri, identify the supporting and inhibiting factors affecting their implementation, and explain the contribution of these strategies to the character development of santri. The study employed a qualitative approach with a case study design. Informants were selected through purposive sampling and included the head of the Islamic boarding school, teachers, dormitory supervisors, and santri directly involved in the implementation of the development programs. Data were collected through observation, semistructured interviews, and documentation and were subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which comprises data condensation, data display, and conclusion drawing and verification. The results showed that Pondok Pesantren Bai’aturridhwan Bukittinggi implemented preventive and educational strategies through restrictions on device use, supervision of santri activities, enforcement of regulations, moral education, teacher role modeling, habituation of religious practices, and the strengthening of digital literacy based on Islamic values. The success of these strategies was supported by the commitment of the leadership, cooperation among all elements of the Islamic boarding school, and a religious environment, whereas barriers to their implementation included rapid technological development, the influence of the external environment, and the diverse characteristics of the santri. These findings confirm that the integration of supervision, religious habituation, role modeling, and digital literacy based on Islamic values contributes to the character development of santri in confronting digital culture. This study strengthens the application of character education theory and strategic management in the context of Islamic education and provides practical implications for Islamic boarding schools in formulating santri development policies that are adaptive to advances in digital technology.